‘매개변수로 나타낸 함수’에 대한 교과서 구성과 교사 인식에 관한 연구 - 양성현(Seong Hyun Yang) (Suhak gyoyukak yeon-gu (Online), 2022)
수학은 다른 어떤 학문보다도 용어의 명료성과 일관성이 중요한 학문이다. 수학 용어는 수학적 개념을 이해하는데 중요한 단서가 될 뿐만 아니라 학습 과정과 학습 후 그 개념과 관련된 이미지를 환기시켜 줄 수 있다. 그러나 학생이 특정 수학 용어에 대하여 오개념이 형성된 경우 환기된 이미지가 본래의 수학적 개념과 잘 부합되는 못하는 상황이 발생할 수 있다. 본고는 교과서에서 사용되고 있는 ‘매개변수로 나타낸 함수’ 표현의 불명료함과 비일관성을 지적하고 이로 인하여 발생되는 교사 인식을 조사하였다. 교사 인식 조사 결과 해당 표현에 대하여 교사들은 다양한 인식을 하고 있었으며 일부 교사들은 수학적 오개념을 가지고 있는 것으로 나타났다. 또한 많은 교사들이 ‘매개변수로 나타낸 함수’ 표현에 대하여 수정의 필요성을 인식하고 있음을 확인하였다. 교과서 및 교사용 지도서가 수학 용어에 대하여 명료성과 일관성을 갖추기 못할 경우 교사는 수학적 개념에 대하여 부정확한 개념을 생성할 수 있으며 이는 학생들에게 직간접적인 영향을 미칠 수 있다. Clarity and consistency of terms are more important in mathematics than in any other discipline. Mathematics terminology can be an essential clue to understanding a mathematical concept. Moreover, it can evoke images related to the concept both during the learning process and after learning. However, the evoked image may fail to match the original mathematical concept accurately if a student has a misconception about a specific mathematical term. This paper specified the ambiguity and inconsistency of the expression “the function represented by a parameter” used in textbooks. Further, it investigated the teachers’ perceptions caused by the phrase. Teacher responses in a survey showed that teachers perceived the words in various ways, and some teachers demonstrated mathematical misconceptions. Additionally, the teachers recognized the need to revise the phrase, “the function represented by a parameter.” Our study implicates that unclear and inconsistent uses of mathematical terms in textbooks and teacher’s guide books might contribute to teacher misunderstandings, which can directly or indirectly affect students. KCI Citation Count: 0